Inhibition of Adherence of Mycobacterium avium to Plumbing Surface Biofilms of Methylobacterium spp. - Mari Carmen Muñoz Egea; Pan Ji; Amy Pruden; Joseph O. Falkinham III (Pathogens, 2017)
Both Mycobacterium spp. and Methylobacterium spp. are opportunistic premise plumbing pathogens that are found on pipe surfaces in households. However, examination of data published in prior microbiological surveys indicates that Methylobacterium spp. and Mycobacterium spp. tend not to coexist in the same household plumbing biofilms. That evidence led us to test the hypothesis that Methylobacterium spp. in biofilms could inhibit the adherence of Mycobacterium avium. Measurements of adherence of M. avium cells to stainless steel coupons using both culture and PCR-based methods showed that the presence of Methylobacterium spp. biofilms substantially reduced M. avium adherence and vice versa. That inhibition of M. avium adherence was not reduced by UV-irradiation, cyanide/azide exposure, or autoclaving of the Methylobacterium spp. biofilms. Further, there was no evidence of the production of anti-mycobacterial compounds by biofilm-grown Methylobacterium spp. cells. The results add to understanding of the role of microbial interactions in biofilms as a driving force in the proliferation or inhibition of opportunistic pathogens in premise plumbing, and provide a potential new avenue by which M. avium exposures may be reduced for at-risk individuals.